Synergy between Mecillinam and Ceftazidime/Avibactam or Avibactam against Multi-Drug-Resistant Carbapenemase-Producing Escherichia coli and Klebsiella pneumoniae - Karoline Knudsen List; Mette Kolpen; Kasper Nørskov Kragh; Godefroid Charbon; Stine Radmer; Frank Hansen; Anders Løbner-Olesen; Niels Frimodt-Møller; Frederik Boetius Hertz (MDPI AG, 2022)
Background: Carbapenemase-producing Klebsiella pneumoniae and Escherichia coli have become a significant global health challenge. This has created an urgent need for new treatment modalities. We evaluated the efficacy of mecillinam in combination with either avibactam or ceftazidime/avibactam against carbapenemase-producing clinical isolates. Materials and methods: Nineteen MDR clinical isolates of K. pneumoniae and E. coli were selected for the presence of blaKPC, blaNDM, blaOXA or blaIMP based on whole-genome sequencing and phenotypic susceptibility testing. We tested the synergy between mecillinam and avibactam or ceftazidime/avibactam. We used time-kill studies in vitro and a mouse peritonitis/sepsis model to confirm the synergistic effect. We investigated avibactam's impact on mecillinam´s affinity for penicillin-binding proteins with a Bocillin assay, and cell changes with phase-contrast and confocal laser scanning microscopy. Results: Mecillinam combined with ceftazidime/avibactam or avibactam substantially reduced MICs (from up to >256 µg/mL to <0.0016 µg/mL) for 17/18 strains. Significant log-CFU reductions were confirmed in time-kill and in vivo experiments. The Bocillin assay did not reveal changes. Conclusion: Mecillinam in combination with avibactam or ceftazidime/avibactam has a notable effect on most types of CPEs, both in vitro and in vivo. The mecillinam/avibactam combination treatment could be a new efficient antibiotic treatment against multi-drug-resistant carbapenemase-producing Gram-negative pathogens.